The importance of correlation among flutter derivatives for the reliability based optimum design of suspension bridges. (15th October 2018) - Kusano, Ibuki; Baldomir, Aitor; Jurado, José Ángel; Hernández, Santiago
Highlights: RBDO applied to suspension bridges under flutter constraint. Definition of correlation among flutter derivatives through experimental tests. Reliability analysis with correlated and uncorrelated flutter derivatives. Unsafe designs may result if these correlations are not taken into account. Effect of this correlation in RBDO results. Abstract: The design of long-span bridges is constrained by the uncertainty in the evaluation of flutter velocity. Among all the elements that take part in the flutter assessment, the uncertainty level in experimentally obtained flutter derivatives has the most impact. It is therefore important in the evaluation of flutter velocity to assess the uncertainty which is associated with the adopted experimental method for flutter derivatives. By using a method of coupled motion only to identify eight flutter derivations simultaneously, it is also essential to consider correlations among the points that define the full set of flutter derivatives since they are not independent from one another. In this research, an experimental campaign was carried out to obtain the statistical information of flutter derivatives and to assemble the correlation matrix. Several cases of reliability analyses were performed to illustrate the importance of considering correlation among random variables as well as the significance of uncertainty level in flutter derivatives on bridge flutter failure. Moreover, a study of Reliability Based Design Optimization (RBDO) was carried out to see the influence of correlations among flutter derivatives on the optimum designs. The RBDO of a suspension bridge was performed under probabilistic flutter constraint using Reliability Index Approach (RIA) method, and this methodology was applied to the Great Belt East Bridge.